Connectivity-preserving flocking for networked Lagrange systems with time-varying actuator faults - Feng, Zhi; Hu, Guoqiang (Automatica (Oxford), 2019)
This paper studies fault-tolerant coordination with connectivity preservation and collision avoidance for unknown Lagrange agent systems subject to actuator faults. In contrast to the existing works, the actuator faults may change the states of the agents to violate the network connectivity and the existence of the loss of effectiveness faults makes control coefficients unknown and time-varying. Furthermore, the leader’s dynamics are allowed to be nonlinear instead of being linear and generated by a marginally stable system. The aforementioned setting improves the practical relevance of the problem to be addressed in the paper and meanwhile, it poses technical challenges to flocking controller design and asymptotic stability analysis. Consequently, for a class of nonlinear leader systems, a novel distributed adaptive scheme is proposed by introducing a distributed estimator and a Nussbaum gain technique to provide a fully distributed solution with guaranteed fault-tolerant coordination, connectivity preservation, and collision avoidance simultaneously. Numerical examples are given to illustrate the effectiveness of the design.